Possibilities of using full homomorphic encryption mechanisms in electronic voting systems - Горбенко, І.Д.; Качко, О.Г.; Горбенко, Ю.І.; Єсіна, М.В.; Кандій, С.О.; Острянська, Є.В.; Д’яченко, А.С. (Radiotekhnika, 2020)
The paper deals with the concept of homomorphic encryption and the possibility of its use in the mechanism of electronic voting. One of the problematic requirements for electronic voting systems is voter anonymity. On the one hand, each voter must be identified, and on the other, the content of his or her vote must be unknown. Currently, the methods and mechanisms used in real voting systems do not provide real anonymity. Therefore, both theoretical and practical content is an urgent and necessary problem of developing mechanisms for anonymous counting of votes with the protection of their distortion. The paper also provides a general analysis of the security level of prospective homomorphic encryption schemes. The essence of homomorphic encryption is that there is some set of operations whose result of executing over ciphertexts (with subsequent decryption) coincides with similar actions over plaintexts. Homomorphic encryption allows you to perform some calculations on information without having access to the information itself. However, there are a number of problems when trying to apply such calculations. The main ones are the choice of the method of asymmetric encryption, which provides the necessary cryptographic stability from both classical and quantum attacks, the identification of possible candidates for asymmetric cryptotransformations in homomorphic encryption, their evaluation of comparison with each other, and, of course, the choice of the most rational for a given multiple restrictions. The asymmetric schemes of homomorphic encryption are compared using the hierarchy analysis process. The method of asymmetric encryption with zero knowledge is substantiated. The objective of this article is to substantiate the possibilities, conditions, and constraints on the use of standardized asymmetric cryptotransformations in the creation of modern homomorphic encryption-type transformations, when anonymity of electronic voting and practical implementation of anonymous voting based on proof of zero knowledge must be guaranteed.